ANALISIS EFEKTIVITAS DAN KONTRIBUSI PAJAK KENDERAAN BERMOTOR TERHADAP PENCAPAIAN TARGET PENDAPATAN ASLI DAERAH PROVINSI ACEH - Fitriya, Rahmatul; Suparno, Suparno (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2019)
Motor vehicle tax is one of the most potential local taxes for Aceh province in improving local income. This research aims to discover the rate of effectiveness of motor vehicle tax acceptance and exact portion of its contribution toward the target of Acehs local own revenues. Kind of data used in this research aresecondary data. They are collected from relevant literatures, websites, and documents which concerned on effectiveness and contribution of the acceptance of motor vehicle tax in Aceh province. The research result shows (1) the effectiveness of motor vehicle tax acceptance towards the target of local own revenues attainment has annual fluctuation which can be categorized as strongly (very) effective from 2013-2014 and effective in 2015. Whereas (2) the contribution of motor vehicle tax acceptance towards the target of local own revenues attainment constantly increase every year, yet it is categorized lack in 2013-2015